Evaluation of volume change in rectum and bladder during application of image-guided radiotherapy for prostate carcinoma - Luna, J.A (2016)
All prostate cancer patients from Centro Médico Radioterapia Siglo XXI receive Volumetric Modulated Arc Therapy (VMAT). This therapy uses image-guided radiotherapy (IGRT) with the Cone Beam Computed Tomography (CBCT). This study compares the planned dose in the reference CT image against the delivered dose recalculate in the CBCT image. The purpose of this study is to evaluate the anatomic changes and related dosimetric effect based on weekly CBCT directly for patients with prostate cancer undergoing volumetric modulated arc therapy (VMAT) treatment. The collected data were analyzed using one-way ANOVA.